Cryoballoon ablation of atrial fibrillation: a practical and effective approach. Issue 5 (19th December 2016) - Georgiopoulos, George; Tsiachris, Dimitris; Manolis, Antonis S.
Abstract : Medical management of atrial fibrillation (AF), the most common arrhythmia in the general population, has had modest efficacy in controlling symptoms and restoring and maintaining sinus rhythm. Since the seminal observation in 1998 that pulmonary veins host the triggers of AF in the majority of cases, electrical isolation of all pulmonary veins constitutes the cornerstone of ablation in patients with symptomatic AF. However, due to the elaborate and tedious technique of the conventional point‐by‐point method with radiofrequency ablation guided by electroanatomical mapping, newer, more versatile single‐shot techniques, such as cryoballoon ablation, have been sought and developed over recent years and are progressively prevailing. Cryoballoon ablation appears to be the most promising practical and effective approach, and we review it here by presenting all available relevant data from the literature as well as from our own experience in an attempt to apprise colleagues of the significant progress made over the last several years in this important field of electrophysiology.